Mie Scattering Captures Observed Optical Properties of Ambient Biomass Burning Plumes Assuming Uniform Black, Brown, and Organic Carbon Mixtures. Issue 21 (6th November 2019) - Chylek, Petr; Lee, James E.; Romonosky, Dian E.; Gallo, Francesca; Lou, Sijia; Shrivastava, Manish; Carrico, Christian M.; Aiken, Allison C.; Dubey, Manvendra K.
Abstract: We use a simple model of a spherical biomass burning aerosol particle containing an internal mixture of black carbon (BC) and organic carbon (OC) with an effective refractive index calculated as a volume fraction‐weighted mean of refractive indices. Brown carbon (BrC) is considered to be an OC with an imaginary part of refractive index at the blue end of the solar spectrum higher (in absolute value) than at the red end. Mie‐scattering formalism is employed to calculate absorption Ångström exponent (AAE) as a function of single‐scattering albedo (SSA) for a set of BC refractive indices, BC volume fraction, and a set of effective refractive indices of BC and BrC mixtures. Ambient plumes are characterized by their mean SSA at 405 nm wavelength and two‐wavelength (405 and 781 nm) AAE values. Comparing observed and model‐calculated AAE and SSA values identifies the BC refractive index and its volume fraction and an effective refractive index of the BC and BrC mixture. From these values, the imaginary part of BrC refractive index is calculated. For observed southwestern ambient fires, the imaginary part of BrC refractive index is ≤0.016. In contrast, fires in the Amazon and from Africa are dominated by BC. We also use the Mie scattering model to establish the upper limit on AAE of BC (AAE ≤ 1.4) and the upper limit of the BC and OC mixture (AAE ≤ 1.7). Any AAE(405/781) > 1.7 requires the presence of BrC. We derive several relationships between AAE, SSA, BC fractions, and an imaginary part of BrC refractive index of ambient fires. Key Points: Mie scattering model assuming spherical aerosol particles captures basic optical properties of ambient biomass burning aerosols Absorption Ångström exponent (AAE) of black carbon is limited to AAE <1.4, and AAE values >1.7 require the presence of brown carbon The imaginary part of refractive index of brown carbon at the blue end of a solar spectrum is found to be between 0.005 and 0.016 for ambient plumes